2016
DOI: 10.1007/s00520-016-3264-5
|View full text |Cite|
|
Sign up to set email alerts
|

Complex management of resistant oral herpes simplex virus infection following hematopoietic stem cell transplantation: potential role of topical cidofovir

Abstract: Topical cidofovir can provide effective management of symptomatic oropharyngeal HSV while reducing risk of systemic toxicity and drug interaction and represents an additional approach to management for management in medically compromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This problem can be overcome by the topical use of cidofovir solution and gel. Successful treatment of ACVr HSV stomatitis by topical cidofovir in HCT patients was described in case reports [9,10,[16][17][18]. Sims et al [10] published data for the topical use of 3% cidofovir oral rinse solution, and Muluneh et al [9] reported the use of topical 1% cidofovir gel in HCT patients.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…This problem can be overcome by the topical use of cidofovir solution and gel. Successful treatment of ACVr HSV stomatitis by topical cidofovir in HCT patients was described in case reports [9,10,[16][17][18]. Sims et al [10] published data for the topical use of 3% cidofovir oral rinse solution, and Muluneh et al [9] reported the use of topical 1% cidofovir gel in HCT patients.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Topical viral infections such as HPV have been reported on bilateral hand transplants, either latent in the donor at the time of procurement or acquired posttransplant, and have been treated with topical cidofovir [35,36]. Topical cidofovir has also proven to be useful in cutaneous HSV cases in VCA transplant patients that, under the influence of immunosuppression and repeated treatment, have become drug-resistant or particularly refractory to treatment [37,38].…”
Section: Skinmentioning
confidence: 99%
“…Ganciclovir and valganciclovir, used for CMV prophylaxis, also have activity against HSV and are protective. Topical cidofovir is also available for reactivated or primary cutaneous cases that become drug-resistant or particularly refractory to treatment [37,38].…”
Section: Nervementioning
confidence: 99%
“…1 Infections caused by human herpes viruses (HHV), such as © 2021 Special Care Dentistry Association and Wiley Periodicals LLC herpes simplex viruses (HSV) 1 and 2 and cytomegalovirus (CMV or HHV-5), may reactivate during the immunosuppression period associated with HSCT. [2][3] HSV infection usually occurs in oral and perioral regions and is associated with high morbidity and mortality in patients with malignant hematological diseases. 2,4 HSV-1 and -2 reactivations are serious post-HSCT complications.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3] HSV infection usually occurs in oral and perioral regions and is associated with high morbidity and mortality in patients with malignant hematological diseases. 2,4 HSV-1 and -2 reactivations are serious post-HSCT complications. HSV-1 is associated with oral infections, whereas HSV-2 usually causes genital lesions, with oral lesions being rare.…”
Section: Introductionmentioning
confidence: 99%